Housing loan rate margins in Finland - Hanna Putkuri (Bank of Finland, 2010)
This paper examines how housing loan rates are determined, using data on new housing loans in Finland. Finland is an example of a bank-based euro area country where the majority of loans are granted at variable rates. The paper extends the earlier interest rate pass-through literature by taking explicitly into account the changing of lending rate margins. A standard lending rate pass-through model, empirically specified as an error-correction model, is extended with variables predicted by a theoretical bank interest rate setting model. The results show that, since the mid-1990s, short-run movements in housing loan rates can be largely explained by changes in money market rates, and that long-run developments have also been affected by less volatile cost and credit risk factors. The roles of loan competition and capital regulation are also considered, but these effects are more difficult to identify empirically.
URN:NBN:fi:bof-20140807348
Keywords: 330